Venous thromboembolic events in hand surgery. Issue 3 (1st June 2021) - Haque, Aziz; Patel, Mohammed S.; Siddiqui, Bobby; Wildin, Clare J.; Dias, Joseph J.
Abstract: The risks of venous thromboembolism (VTE) following total hip and knee arthroplasty have been widely published. Our aim was to investigate the recorded incidence of VTE events at the time of elective and trauma hand surgery. The UK National Hospital Episode Statistics (HES) data linking VTE events with hand surgery for the financial years 2010–2012 were analysed. The local VTE rates following hand surgical procedures were also analysed. Finally, a cost assessment of VTE thromboprophylaxis was performed according to the British Society for Surgery of the Hand (BSSH) guidelines. 334, 211 hand surgical procedures were performed throughout England of which there were 13 DVT and 27 PE events. These events were seen in patients with pre-existing comorbidities. The annual incidence of VTE is 0.006% at most in hand surgical patients in England. The cost of implementing mechanical VTE thromboprophylaxis to all patients having hand surgery would amount to £6, 336, 641 over 2 years. The cost of treatment for all VTE events would amount to £20, 418. VTE prophylaxis is probably not necessary in patients undergoing isolated elective or trauma hand surgical procedures.